2017
DOI: 10.1038/srep45679
|View full text |Cite
|
Sign up to set email alerts
|

The role of motion and number of element locations in mirror symmetry perception

Abstract: The human visual system has specialised mechanisms for encoding mirror-symmetry and for detecting symmetric motion-directions for objects that loom or recede from the observers. The contribution of motion to mirror-symmetry perception has never been investigated. Here we examine symmetry detection thresholds for stationary (static and dynamic flicker) and symmetrically moving patterns (inwards, outwards, random directions) with and without positional symmetry. We also measured motion detection and direction-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
24
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 70 publications
11
24
2
Order By: Relevance
“…Using dynamic dot-patterns refreshed at 65 Hz, Tyler et al [31,32] have investigated the effect of eccentricity on symmetry perception and found that static stimuli produced superior performance compared to dynamic stimuli, with static symmetry being perceived more quickly and further into the periphery. This is in contrast to more recent studies showing better performance with dynamic than static patterns [18,33]. Studies have shown that using dynamic stimuli consisting of rapid successive presentations of different symmetrical patterns improves symmetry detection [18] and orientation discrimination of the symmetry axis [33].…”
Section: Introductioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Using dynamic dot-patterns refreshed at 65 Hz, Tyler et al [31,32] have investigated the effect of eccentricity on symmetry perception and found that static stimuli produced superior performance compared to dynamic stimuli, with static symmetry being perceived more quickly and further into the periphery. This is in contrast to more recent studies showing better performance with dynamic than static patterns [18,33]. Studies have shown that using dynamic stimuli consisting of rapid successive presentations of different symmetrical patterns improves symmetry detection [18] and orientation discrimination of the symmetry axis [33].…”
Section: Introductioncontrasting
confidence: 89%
“…This is in contrast to more recent studies showing better performance with dynamic than static patterns [18,33]. Studies have shown that using dynamic stimuli consisting of rapid successive presentations of different symmetrical patterns improves symmetry detection [18] and orientation discrimination of the symmetry axis [33]. It has been suggested that these improvements in performance are due to multiple weak or noisy neural responses to symmetry being integrated over time to generate a stronger response.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although detection of reflectional symmetry is not affected by number of elements, Sharman and Gheorghiu found that dynamic flicker or motion of the elements improves symmetry detection. This was consistent with previous work by Niimi et al .…”
Section: Visual Processing Of Symmetry and Its Role In Figure–groundmentioning
confidence: 99%